Integration and Labour Markets in European Border regions - Annekatrin Niebuhr; Silvia Stiller (European Regional Science Association (ERSA), 2004)
Border regions are likely to play a critical role within the special dynamics initiated by the enlargement of the EU. This paper deals with the effects of integration on labour market conditions in border regions. Within the framework of different theoretical approaches the effects of integration on location conditions and labour markets in border regions are analysed. Furthermore, we investigate empirically the degree of labour market integration in European border regions. Measures of spatial association are applied as indicators for the intensity of integration among neighbouring labour markets. The results of an analysis of per capita income and unemployment for the period 1995 to 2000 point at a measurable spatial segmentation of labour markets even among highly integrated EU15 countries. On average, border regions in the EU are characterised by lower degree of labour market integration than non-border areas due to significant border impediments that hamper equilibrating forces between labour markets on both sides of national frontiers. JEL classification: F22, J61, R23 Keywords: European Integration, Labour Market Disparities, Border Regions, Spatial Dependence
Keywords: F22; J61; R23; 330; European Integration; Labour Market Disparities; Border Regions; Spatial Dependence